Trends and Landscape of Omnibus Law Research: A Bibliometric Analysis - Kususiyanah, Anjar; Chairul Huda, Muhammad; Sriwidodo, Joko; Baharuddin, Ahmad Syukran (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
The Omnibus Law in Indonesia has generated significant controversy due to its far-reaching effects on legal, economic, and social dimensions, particularly regarding worker rights and the balance of business interests. This study aims to deliver a thorough review of the Omnibus Law through a systematic approach, providing a valuable resource for researchers, policymakers, and stakeholders. Utilizing bibliometric analysis and systematic literature review methods, we analyzed 64 articles from Scopus, employing visualization tools such as VOSviewer and R-Studio to identify publication trends. Our analysis shows a global rise in interest in the Omnibus Law, with a notable increase in publications post-2020 and substantial engagement from international researchers. The results indicated that 40.6% of the articles supported the Omnibus Law, 37.5% opposed it, and 21.9% maintained a neutral stance. While the majority of articles favored the law, the significant number of critical perspectives underscores the necessity for a more in-depth examination, especially regarding worker rights. Key concerns include the law's approach to minimum wage, alignment with Islamic values, institutional integrity, and potential biases favoring businesses. We recommend establishing a wage mechanism that reflects living standards and inflation, as well as engaging Islamic legal experts to protect worker rights. Additionally, the Omnibus Law addresses issues beyond labor, such as climate change, legal protections, forest dynamics, and transparency, highlighting its extensive implications for Indonesia and opening numerous avenues for future research.